2018
DOI: 10.1002/term.2713
|View full text |Cite
|
Sign up to set email alerts
|

Biofabrication of a novel leukocyte-fibrin-platelet membrane as a cells and growth factors delivery platform for tissue engineering applications

Abstract: Autologous platelet-rich hemocomponents have emerged as potential biologic tools for regenerative purpose, but their therapeutic efficacy still remains controversial. This work represents the characterization study of an innovative autologous leukocyte-fibrin-platelet membrane (LFPm), which we prepared according to a novel protocol involving multiple cycles of apheresis. The high content in fibrinogen gave to our hemocomponent the appearance of a manipulable and suturable membrane with high elasticity and defo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…However, it is important to emphasize that there has never been any published evidence demonstrating that a PRF membrane can maintain spaces for tissue regeneration for sufficient periods of time because of its rapid degradability (Kawase et al, ). Specific in vitro/in vivo analyses of biodegradation profiles of fibrin membranes have been rarely reported in literature (Barbon et al, ). Kawase et al, (), demonstrated that L‐PRF was completely resorbed within 2 weeks after subcutaneous implantation in nude mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to emphasize that there has never been any published evidence demonstrating that a PRF membrane can maintain spaces for tissue regeneration for sufficient periods of time because of its rapid degradability (Kawase et al, ). Specific in vitro/in vivo analyses of biodegradation profiles of fibrin membranes have been rarely reported in literature (Barbon et al, ). Kawase et al, (), demonstrated that L‐PRF was completely resorbed within 2 weeks after subcutaneous implantation in nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…Kawase et al, (), demonstrated that L‐PRF was completely resorbed within 2 weeks after subcutaneous implantation in nude mice. Barbon et al, (), produced a innovative autologous leukocyte‐fibrin‐platelet membrane (LFPm), which was prepared according to a novel protocol involving multiple cycles of apheresis. The biodegradation analysis showed a good stability of the membrane for only 1 week in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The final membrane is highly enriched with platelets, leukocytes, monocytes/macrophages, fibrinogen, and CD34 + cells. Our research group performed a detailed in vitro characterization of the CLP-MB membrane, highlighting its regenerative properties in terms of GF release, mechanical behavior and biodegradation profile [12]. The CLP-MB exhibits good elasticity and high deformation capacity, demonstrating itself to be suitable for implantation in the Knee joint for articular cartilage repair.…”
Section: Prf In Cartilage Tissue Engineeringmentioning
confidence: 99%
“…Moreover, this blood-derived membrane is enriched with leukocytes, which play a key role not only in immune and antibacterial responses, but also in the wound healing process [7,8]. Since Choukroun’s PRF was first described, many variations of the original protocol have appeared, resulting in the production of PRF-like materials with different architectures and cell contents [9,10,11,12,13,14,15,16,17]. The fundamental challenge to be overcome remains the concentration of platelets, which should be increased to a minimum of 5 times above baseline values for the hemocomponent to be considered “platelet rich” [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation